The implications of high energy and carbon prices on firms - Aykut Mert Yakut; Samuel McArdle; Kelly C. De Bruin (The Economic and Social Research Institute (ESRI), 2024)
Transitioning to a low-carbon economy requires undertaking massive investment expenditures, and how to finance these expenditures remains at the core of economic debates. However, the cost of not transitioning to a low-carbon economy is often forgotten in these debates. These costs have increased under current global geopolitical tensions, especially for imported fossil fuel-dependent countries, such as Ireland. This report aims to quantify the cost of decarbonisation inaction. What costs will Irish firms face if they continue with their current energy use patterns when the carbon tax (set by the Irish government) and the European Union Emissions Trading System (EU ETS) price (determined by the market conditions at the EU level) are increasing while at the same time, international energy prices are at their extremely high levels?
Keywords: 330